Do anthropometric and fitness characteristics vary according to birth date distribution in elite youth academy soccer players? - Carling, C.; Le Gall, F.; Reilly, T.; Williams, A. M. (Scandinavian Journal of Medicine & Science in Sports, 2009)
We examined whether maturity, anthropometric profiles and fitness measures vary according to birth date distribution in elite, under-14 youth academy soccer players. The selection year was divided into four quarters, with 160 male players grouped according to individual birth date. Players had their skeletal age determined and were assessed using a battery of standard anthropometric and physical performance tests. Players born across all quarters of the year were investigated for differences in the various performance characteristics using multi- and univariate analyses. An uneven birth distribution was observed, with players born early in the selection year highly represented (P<0.01). A significant difference in height was observed across quarters (P<0.01) with higher values reported in the earlier-born players. No significant differences were observed across any of the fitness measures, although the trend was for players born in the first quarter to out-perform peers born in the later quarters. These findings suggest that the relative age of the performer may not always be linked to a significant advantage in physical components. The selection criteria for entry into the academy may explain the present results.